1998
DOI: 10.1021/je970233e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Liquid Viscosities of Decane and Octane + Decane from 298.15 K to 373.15 K and Up to 25 MPa

Abstract: Experimental liquid viscosities of decane and of a binary mixture of octane + decane have been measured using a rolling ball viscometer at temperatures from 298.15 K to 373.15 K and at pressures up to 25 MPa. The mixture measurements agree with literature values within an average value of 1.2%. Deviations of the results from existing correlations are within 2.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 23 publications
7
23
1
Order By: Relevance
“…From these deviations, we can also conclude that the experimental data are internally consistent to within the estimate experimental uncertainty. Equation (16) Figure 7, we compare the new results with data from the literature [13][14][15][16][17][18][19] at pressures up to 10 MPa as deviations from the correlation of Tariq et al 1 Our results agree well with the majority of the experimental data reported in the literature; however, the data of Rajagapol et al 17 at temperatures below 400 K and those of Grachev et al 19 to constrain the behavior of their correlation in the liquid state at temperatures above 441 K and those data are systematically higher than ours at temperatures above 450 K. Figure 8 compares our new results with data from the literature 13,14,[20][21][22][23][24][25][26][27][28][29] at pressure up to 10 MPa as deviations from the correlation of Huber et al 2,3 At temperatures up to 500 K, our new data agree with the correlation to within about ±1 %, which is the stated uncertainty of the correlation for the saturated liquid. At higher temperatures, the deviations are somewhat dependent upon pressure and span the interval (-3 to -6) %.…”
Section: Correlation Of the Viscosity Ratios At Low Temperatures Thsupporting
confidence: 90%
“…From these deviations, we can also conclude that the experimental data are internally consistent to within the estimate experimental uncertainty. Equation (16) Figure 7, we compare the new results with data from the literature [13][14][15][16][17][18][19] at pressures up to 10 MPa as deviations from the correlation of Tariq et al 1 Our results agree well with the majority of the experimental data reported in the literature; however, the data of Rajagapol et al 17 at temperatures below 400 K and those of Grachev et al 19 to constrain the behavior of their correlation in the liquid state at temperatures above 441 K and those data are systematically higher than ours at temperatures above 450 K. Figure 8 compares our new results with data from the literature 13,14,[20][21][22][23][24][25][26][27][28][29] at pressure up to 10 MPa as deviations from the correlation of Huber et al 2,3 At temperatures up to 500 K, our new data agree with the correlation to within about ±1 %, which is the stated uncertainty of the correlation for the saturated liquid. At higher temperatures, the deviations are somewhat dependent upon pressure and span the interval (-3 to -6) %.…”
Section: Correlation Of the Viscosity Ratios At Low Temperatures Thsupporting
confidence: 90%
“…The third binary system studied in this work contains (nC 8 +nC 10 ). The experimental viscosity data for this binary mixture are from Estrada-Baltazar et al [18]. The present model is used in order to reproduce viscosities in the temperatures ranged (297.95-373.35) K and pressures ranged (1.01-246.26) bar.…”
Section: Results and Discussion 31 Binary Mixturesmentioning
confidence: 99%
“…Since the viscometer constant shows temperature and pressure dependences, it should be determined at each temperature and pressure. Estrada-Baltazar et al expressed K as a polynomial equation on temperature and pressure [5]. However, this method needs many experiments over a wide range of temperature and pressure.…”
Section: Methodsmentioning
confidence: 99%